2014
DOI: 10.1093/pcp/pcu098
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression of a Loblolly Pine Class II 4-Coumarate:CoA Ligase Alters Soluble Phenylpropanoid Metabolism but not Lignin Biosynthesis in Populus

Abstract: 4-Coumarate:CoA ligase (4CL) catalyzes the formation of hydroxycinnamoyl-CoA esters for phenylpropanoid biosynthesis. Phylogenetically distinct Class I and Class II 4CL isoforms occur in angiosperms, and support lignin and non-lignin phenylpropanoid biosynthesis, respectively. In contrast, the few experimentally characterized gymnosperm 4CLs are associated with lignin biosynthesis and belong to the conifer-specific Class III. Here we report a new Pinus taeda isoform Pinta4CL3 that is phylogenetically more clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Previous phylogenetic analysis shows that the four Arabidopsis 4CLs belong to two distinct classes (Ehlting et al, 1999;Soltani et al, 2006;Chen et al, 2014); however, the scope of these phylogenetic analyses was limited to a few plant species. Using the four Arabidopsis 4CLs as query, we identified 192 4CL protein homologs from across the plant kingdom with 70% or more sequence identity to at least one of the Arabidopsis proteins, and generated a new phylogenetic tree using Bayesian analysis (Fig.…”
Section: Phylogenetic Analysis Of 4cl Homologsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous phylogenetic analysis shows that the four Arabidopsis 4CLs belong to two distinct classes (Ehlting et al, 1999;Soltani et al, 2006;Chen et al, 2014); however, the scope of these phylogenetic analyses was limited to a few plant species. Using the four Arabidopsis 4CLs as query, we identified 192 4CL protein homologs from across the plant kingdom with 70% or more sequence identity to at least one of the Arabidopsis proteins, and generated a new phylogenetic tree using Bayesian analysis (Fig.…”
Section: Phylogenetic Analysis Of 4cl Homologsmentioning
confidence: 99%
“…In addition, their expression patterns are different in that one is expressed highly in the root, whereas the other is in the stem (Li et al, 2014). Functional analysis showed that Pinta4CL1 and Pinta4CL3 from loblolly pine have similar catalytic efficiencies toward p-coumaric acid and caffeic acid; however, Pinta4CL1 has the highest expression in xylem, where it presumably has a role in lignin biosynthesis, and Pinta4CL3 functions mainly in the biosynthesis of soluble metabolites (Chen et al, 2014). Similarly, a recent study showed that 4CL1 in Populus spp.…”
Section: Isoforms Of 4cl Have Diverged In Functionmentioning
confidence: 99%
“…A second gene, 4CL2 (Potri.019G049500) that is phylogenetically distinct from lignin-associated 4CLs (Chen et al., 2014 ). was also targeted in the study.…”
Section: High-efficiency Genome Editing Of Populusmentioning
confidence: 99%
“…As with the 4CL1 case, biallelic mutations were observed in all independent transgenic lines surveyed by amplicon-sequencing (Zhou et al., 2015 ). The metabolic consequence was examined in roots where flavonoid-derived condensed tannins (CTs) are known to accumulate to high levels (∼20% dry weight) in the experimental poplar genotype (Chen et al., 2014 ). CRISPR/Cas9 mutations of 4CL2 resulted in significantly reduced levels of condensed tannins in roots, providing reverse genetics evidence in support of Class II 4CL function in flavonoid biosynthesis.…”
Section: High-efficiency Genome Editing Of Populusmentioning
confidence: 99%
“…In recent years, research into lignin synthesis have mainly focused on the metabolic pathway of phenylpropanoid compounds and lignin-specific biosynthesis. These studies have shown that the activities of enzymes like phenylalanine ammonia-lyase (PAL), cinnamate 4-hydroxylase (C4H), 4-coumarate-CoA ligase (4CL), cinnamyl alcohol dehydrogenase (CAD), and cinnamoyl-CoA reductase (CCR) are closely related to the total amount of lignin synthesis in flax fibers [3]. The reduction of PAL activity in transgenic tobacco decreases its lignin content, but this mutation also affects the normative growth of the plant [4].…”
Section: Introductionmentioning
confidence: 99%